SCHOOLING DETECTION OF PELAGIG FISH USING HYDROACOUSTIC METHOD IN TOBA LAKE, NORTH SUMATERA - Syafri Riki; Alit Hindri Yani; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Schooling is the most important structure in the life of several pelagic fish populations. Pelagic fish can form a very large schooling so that it is one of the abundant fisheries resources in general waters (Welcome R. L, 2001). Because of this, fishermen can use the schooling to catch large amounts of pelagic fish. An effective method for detecting fish schooling is one of hydroacoustic methods. The purpose of this study was to detect pelagic fish schooling in Lake Toba waters in order to provide an accurate picture of the insitu conditions of the potential resources of Pelagic fish in Lake Toba. The data or material used in this study is the acoustic data of Lake Toba waters that have been recorded during the shipping period with a ship speed of 7-10 knots using a scientific echosounder biosonic DT-X Spilt Beam 200 kHZ. The results showed the distribution of pelagic fish schooling was detected at a depth of 5-110 meters as many as 36 fish schooling, the highest detected at depths of 1-10 meters as many as 11 fish schooling and the lowest 1 schooling at a depth of 50-60 meters. Based on time, the distribution of fish schooling in Lake Toba waters was detected at morning, afternoon and evening. In the morning 6 fish schooling were detected, noon 18 fish schooling and 12 fish schooling in the afternoon. Keywords: Detection, Schooling Fish, Hydroacoustic, Pelagic Fish